2019
DOI: 10.3390/s19235227
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Biomechanical Time-Series with Wearable Sensors: A Systematic Review of Machine Learning Techniques

Abstract: Wearable sensors have the potential to enable comprehensive patient characterization and optimized clinical intervention. Critical to realizing this vision is accurate estimation of biomechanical time-series in daily-life, including joint, segment, and muscle kinetics and kinematics, from wearable sensor data. The use of physical models for estimation of these quantities often requires many wearable devices making practical implementation more difficult. However, regression techniques may provide a viable alte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 110 publications
(233 reference statements)
1
39
0
Order By: Relevance
“…Inertial measurement unit (IMU) sensors are gaining traction as a clinical gait analysis tool due to their improved accuracy, feasibility, ease-of-use, and importantly, applicability outside of the laboratory environment [ 1 , 2 ]. A meta-analysis of inertial sensor based gait analysis research concluded limited evidence in their application for determining joint kinematics, especially in non-sagittal (flexion-extension) motion [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inertial measurement unit (IMU) sensors are gaining traction as a clinical gait analysis tool due to their improved accuracy, feasibility, ease-of-use, and importantly, applicability outside of the laboratory environment [ 1 , 2 ]. A meta-analysis of inertial sensor based gait analysis research concluded limited evidence in their application for determining joint kinematics, especially in non-sagittal (flexion-extension) motion [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of methods have been proposed for this purpose, and reviewed by Ancillao et al [ 9 ]. To overcome accuracy limitations and the restricted subsets of parameters that can be determined, researchers have focused on applying machine learning methods to improve the prediction of GRFs, joint angles and joint moments [ 2 , 10 , 11 , 12 , 13 , 14 , 15 ], with initial efforts focused on predicting smaller subsets of data, such as single GRF and joint moment components [ 10 , 11 , 12 ], or in the case of Stetter et al [ 13 ] by predicting sagittal and frontal plane moments in isolation. Very recently gait researchers have trained machine learning models to predict all component joint angles [ 14 , 15 ] and moments across all lower limb joints [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach is for now limited to the determination of the 2D joint angles [ 13 , 14 ]. The use of machine learning, in particular, artificial neural networks, is gaining more and more relevance in biomechanical time-series estimation and has recently been reviewed by Gurchiek et al [ 15 ]. They found hybrid approaches incorporating domain knowledge by feature selection into the model to be helpful for accurate predictions.…”
Section: Introductionmentioning
confidence: 99%
“…While physics-based techniques exist for estimating these clinically relevant variables from wearables [20], [21], they require complex sensor arrays that discourage use outside of research contexts [22]. Regression algorithms have been proposed to reduce the number of required sensors [23], but at…”
mentioning
confidence: 99%